Chemical characteristics of mineral trioxide aggregate and its hydration reaction - Seok-Woo Chang (Korean Academy of Conservative Dentistry, 2012)
Mineral trioxide aggregate (MTA) was developed in early 1990s and has been successfully used for root perforation repair, root end filling, and one-visit apexification. MTA is composed mainly of tricalcium silicate and dicalcium silicate. When MTA is hydrated, calcium silicate hydrate (CSH) and calcium hydroxide is formed. Formed calcium hydroxide interacts with the phosphate ion in body fluid and form amorphous calcium phosphate (ACP) which finally transforms into calcium deficient hydroxyapatite (CDHA). These mineral precipitate were reported to form the MTA-dentin interfacial layer which enhances the sealing ability of MTA. Clinically, the use of zinc oxide euginol (ZOE) based materials may retard the setting of MTA. Also, the use of acids or contact with excessive blood should be avoided before complete set of MTA, because these conditions could adversely affect the hydration reaction of MTA. Further studies on the chemical nature of MTA hydration reaction are needed.